Resource-based view model implementation toward business competitiveness (Case study in mushroom SMEs in Malang, Indonesia) - Ardaneswari Dyah Pitaloka Citraresmi; Andan Linggar Rucitra; Novi Haryati; Faizatul Amalia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Mushroom is one of the main commodities of agroindustry which experienced an increase in production due to the existence of consumer awareness to consume healthy products. The popularity causes the development of the mushroom processing industries in Malang. To improve the quality of products, mushroom SMEs need to further develop the company performance. Company performance can be achieved with an effective competitive advantage. Competitive advantage is a factor that a company should have in order to succeed in business. The fundamental source of competitive advantage is assets. This research use a Barney’s theory in determining strategic resources to achieve competitive competitiveness called Resource-Based View (RBV). The purpose of this research are to determine the influence of: (1) tangible assets on competitive advantage strategy, (2) intangible assets on competitive advantage strategy, (3) company capability on competitive advantage strategy, and (4) competitive advantage strategy on company performance. The exploration techniques utilised are quantitative and Partial Least Square (PLS). The results showed that the tangible assets and company capability have a strong influence and positively contribute to competitive advantage strategy, meanwhile intangible assets have a weak influence and negatively contribute to competitive advantage strategy, and competitive advantage strategy has a strong influence and positively contributes to company performance.